ANALISIS MOTIVASI SISWA PADA PROGRAM ILMU SOSIAL DALAM MEMILIH LINTAS MINAT BIOLOGI DI SMAN KUBU DAN SMAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Arnentis Arnentis; Febblina Daryanes; Elya Febrita; Eka Emariza (Bioilmi: Jurnal Pendidikan, 2022)
This study aims to determine the motivation of students in the social science program in choosing cross-interest in Biology at SMAN Kubu and SMAN Kubu Babussalam, Rokan Hilir Regency. The type of research is descriptive research. The research was conducted at SMAN 1 Kubu, SMAN 1 Kubu Babussalam and SMAN 2 Kubu Babussalam. The time of the study started from August to October 2020. The sample was determined using a purposive sampling technique. The sample in the study were 35 students from SMAN 1 Kubu, 36 students from SMAN 1 Kubu Babussalam, 38 students from SMAN 2 Kubu Babussalam with a total of 109 people. Data collection by distributing questionnaires online through the Google Forms Platform. Data were analyzed descriptively. The results showed that the average student motivation in the social science program in choosing cross-interest biology at SMAN 1 Kubu was 73% with the "High" category, SMAN 1 Kubu Babussalam was 76% with the "High" category, SMAN 2 Kubu Babussalam was 74 % with the category “High”. The average for indicators of student motivation in social science programs in choosing cross-interest biology in the three schools is 74% with the High category.